Adolescent Friendships, BMI, and Physical Activity: Untangling Selection and Influence Through Longitudinal Social Network Analysis. (19th August 2013) - Simpkins, Sandra D.; Schaefer, David R.; Price, Chara D.; Vest, Andrea E.
<x xml:space="preserve">Abstract</x> Bioecological theory suggests that adolescents' health is a result of selection and socialization processes occurring between adolescents and their microsettings. This study examines the association between adolescents' friends and health using a social network model and data from the National Longitudinal Study of Adolescent Health (N = 1, 896, mean age = 15.97 years). Results indicated evidence of friend influence on BMI and physical activity. Friendships were more likely among adolescents who engaged in greater physical activity and who were similar to one another in BMI and physical activity. These effects emerged after controlling for alternative friend selection factors, such as endogenous social network processes and propinquity through courses and activities. Some selection effects were moderated by gender, popularity, and reciprocity.